Structured Repetition and Student Discipline as Mechanisms of Qur'an Memorization Quality: Evidence from a Tahfidz Program in Indonesian Pesantren - Irna Liwa'ul Jannah; Iva Inayatul Ilahiyah (Dirasah : Jurnal Studi Ilmu dan Manajemen Pendidikan Islam, 2026)
Qur'an memorization programs in Islamic boarding schools (pesantren) frequently encounter the challenge of memorization degradation due to inconsistent review practices and the absence of systematic discipline structures. This study investigated the implementation of discipline-based muroja'ah (systematic Qur'an memorization review) and its effects on memorization quality at Pondok Pesantren Faidlul Qur'an Bendungrejo Jogoroto, Jombang, Indonesia. A qualitative case study design was employed, with 9 purposively selected participants comprising one pesantren director, two tahfidz supervisors, and six active students holding a minimum of five juz of memorized Qur'an. Data were generated through participant observation, semi-structured in-depth interviews, and document analysis, and were analyzed using the Miles and Huberman thematic framework. Trustworthiness was established through source and method triangulation and member-checking. The findings reveal that discipline-based muroja'ah operates through three interlocking mechanisms: (1) structured scheduling with tiered daily targets calibrated to individual juz levels; (2) a dual discipline system integrating externally enforced regulations with progressively internalized student self-discipline; and (3) a systematic supervision and evaluation cycle using setoran (submission) cards and corrective feedback records. These mechanisms collectively produced demonstrable improvements in memorization quality across three dimensions fluency, recitation accuracy, and tajwid compliance while simultaneously fostering the character traits of discipline, responsibility, and istiqamah (consistency). The study contributes an empirically grounded operational model of discipline-integrated muroja'ah that extends existing memorization theory by specifying the structural conditions under which repetition-based methods achieve sustained effectiveness